The influence of sound and vision in sensory marketing towards customer purchasing behaviour in institutional foodservice / Munirah Mohammed Shaed ... [et al.] - Mohammed Shaed, Munirah; Tamby Chik, Chemah; Aini, Noorsyamimi; Nongchik, Nurulhuda (2015)
The purpose of the research study is to create a general awareness for specific promotional tools using multi senses which are sound and vision and how it influence customer purchasing behaviour in institutional foodservice specifically in cafeterias. Even though markets and retailers start to apply sensory marketing, there is still limited academic research investigating its effect on consumer be-haviour. This research study is aimed to describe the relationship between these factors and how each of the factors could affect the customers’ purchasing behaviour in institutional cafeterias. In ad-dition, they would explore on the behavioural of customer towards sensory marketing tools such sounds and vision. This research had revealed on the impact of sensory marketing towards customer be-haviour through the correlation between the independent variables towards dependent variables. Furthermore, it would be used as ref-erences for the marketers and entrepreneur who would interest en-tering foodservice business especially in institutional cafeteria.